2020
DOI: 10.1002/pon.5595
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pain and its association with symptoms of post‐traumatic stress disorder, depression, anxiety and distress in 846 cancer patients: A cross sectional study

Abstract: Objective Pain depicts a severe physical symptom but its relationship to mental health problems is not well studied in cancer patients. The aim of this study was to investigate the prevalence of pain and its correlation with symptoms of post‐traumatic stress disorder (PTSD), depression, anxiety and psychological distress in a large sample of cancer patients. Methods From 2010 to 2019, cancer patients who received outpatient treatment at the Medical University of Vienna were assessed with the Post‐Traumatic Sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Due to excessive worry, sadness, and fear of the disease [11,12], the possibility of psychological disorders was significantly increased. Previous studies had pointed out that the detection rate of psychological pain could reach more than 35% in the study of patients with tumor diseases [13][14][15]. Psychological pain was often ignored in clinical practice, but in the study of patients, psychological pain often caused the pain of clinical organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Due to excessive worry, sadness, and fear of the disease [11,12], the possibility of psychological disorders was significantly increased. Previous studies had pointed out that the detection rate of psychological pain could reach more than 35% in the study of patients with tumor diseases [13][14][15]. Psychological pain was often ignored in clinical practice, but in the study of patients, psychological pain often caused the pain of clinical organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous findings have demonstrated that trauma-exposed individuals can show diverse negative psychological reactions (Liang et al, 2021;Unseld et al, 2020). However, these studies have typically depended on the co-occurring patterns of PTG and one negative psychological outcome, such as PTSD, to determine growth (J.…”
mentioning
confidence: 99%
“…Certain people are relatively more likely to detect and consciously perceive symptoms. Stress and depression influence the response to symptoms ( 39 , 40 ). In a prior study, an improvement in the symptoms of depression was significantly associated with improvements in autonomous self-care behaviors ( 41 ).…”
Section: Discussionmentioning
confidence: 99%